POST OPERATIVE WOUND INFECTION IN UNCOMPLICATED LAPAROSCOPIC CHOLECYSTECTOMY WITH AND WITHOUT A DRAIN: Wound Infection in Uncomplicated Laparoscopic Cholecystectomy - Bangash, Tajamul Hussain; Siddique, Muhammad Khalid; Imran, Muhammad; Fatima, Wajiha; Kamran, Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the frequency of wound infection with and without subhepatic drain in patient’s undergoing laparoscopic cholecystectomy. Study Design: Randomized controlled trial. Place and Duration of Study: Study was carried out at department of Surgery, Combined Military Hospital (CMH) Lahore, from Nov 2014 to Apr 2015 over a period of six months. Material and Methods: This study included a total of 140 patients (70 in each group). In group A, a drain was placed in subhepatic space after laparoscopic cholecystectomy and no drain was placed in group Bafter laparoscopic cholecystectomy. Results: In our study, out of 140 patients (70 in each group), patients in the age range of 20-50 years were 61.43% (n=43) in group-A and 57.14% (n=40) in group-B while those in the age range of 51-70 years were 38.57% (n=27) in group-A and 42.86% (n=30) in group-B. Mean ± SD was found to be 46.34 ± 7.54 and 46.23 ± 10.34 years respectively. About 28.57% (n=20) in group-A and 22.86% (n=16) in group-B were male while 71.43% (n=50) in group-A and 77.14% (n=54) in group-B were females. Wound infection was compared in both groups which showed that 18.57% (n=13) in group-A and 7.14% (n=5) in group-B had wound infection. A p-value was calculated as 0.04 which was significant. Conclusion: We concluded that the frequency of wound infection with subhepatic drain in patients undergoing laparoscopic cholecystectomy was found significantly higher when it was compared to cases without drain.